Recent Advances in Biostatistics (IntechOpen, 2024)
This one-of-a-kind volume explores the most recent advancements in biostatistics and its applications. Among the chapters included are both original contributions and reviews of the most recent advancements in the field. Written by researchers from the pharmaceutical industry, universities, and the research and development divisions of the government, this book offers a balanced representation of the research community. It provides advanced graduate students and new researchers with a complete scholarly assessment of several research frontiers in biostatistics and will help these readers make significant contributions to the development of the subject by exploring new approaches and making discoveries.